HUBUNGAN KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH DAN EFIKASI DIRI DENGAN KINERJA MENGAJAR GURU SMP NEGERI DI KECAMATAN PINANG RAYA - Deni Afrina; Rohiat Rohiat; Zakaria Zakaria (UNIVERSITAS BENGKULU, 2018)
AbstractThis study aims to reveal the relationship of principal instructional leadership and self efficacy with the performance of teaching teachers of public junior high school in Pinang Raya District. The research method that will be used in the preparation of this thesis is survey research with quantitative approach. The survey research is to explain the casual relationship and hypothesis testers. Collection data using questionnaires, which have completed scores on each item. While the data analysis techniques used to test the hypothesis is a simple linear correlation analysis technique and multiple correlation. Based on the results of the study, the conclusions can be drawn from the results of this study is the teacher's teaching performance can be improved by improving principal instructional leadership performance and self efficacy Keywords: Teacher’s Teaching performance (Y) , Principal Instructional Leadership (X1) and Self-efficacy (X2)